Earnings Management Moderation in the Effect of Company Performance on Impression Management with Firm Size as a Control Variable - Gary Limbong, Kevin (Journal La Sociale, 2025)
management, considering the role of earnings management as a moderating variable and firm size as a control variable. The object of the study is the banking sector listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. Firm performance is measured by Return on Assets (ROA), earnings management by discretionary accruals, and impression management through content analysis of the MD&A section in annual reports. The results show that firm performance has a negative effect on impression management, and earnings management weakens this relationship. Firm size also influences the tendency to use impression management strategies. These findings contribute to the understanding of managerial behavior in financial reporting.